Factors influencing consumers’ intention to use cashless payment among Public University’s undergraduate students - Chai, Wen Jing; Othman, Mohd Amim; Hashim, Ahmad Hariza (Human Resource Management Academic Research Society, 2024)
The main objective of this study is to determine factors influencing consumers' intention to use cashless payment among undergraduate students in Public University. A total of 200 undergraduate students were involved in this study selected through simple random sampling. Questionnaires were distributed using Google Forms and the Statistical Package for Social Science was employed to analyze the collected data. Mean was used to identify the level of consumers' intention to use cashless payment and multiple linear regression analysis was used to identify the predictor that influences consumers' intention to use cashless payment. The results of this study showed that there is a high level of intention to use cashless payment (mean score=4.319). Multiple linear regression analysis indicated that perceived usefulness (p<0.001), trust (p<0.001) and perceived ease of use (p<0.002) is the significant predictors for intention to use cashless payment in the future (adjusted R2=0.544). This shows that the predictor factors ability to explain influencing intention to use cashless payment is as high as 54.4 percent. The study's findings have increased understanding of the intention to use cashless payment, Technology Acceptance Model (TAM) and its theoretical and practical implications. In conclusion, perceived usefulness, trust and perceived ease of use as predictor variables influence consumer’ intention to use cashless payment among undergraduate students in Public University.